FECUNDITY AND SPAWNING HABITS OF SOME SILVER-BELLIES - Pillai, P K Mahadevan (Indian Journal of Fisheries, 2011)
The results of fecundity and ova diameter frequency studies on four speciesof silver-bellies, viz., Secutor insidiator, S. ruconius, Leiognathus dussumieri andGazza minuta are presented. The former three species seem to have a prolongedspawning seaon, while the last one has a restricted spawning period.